Error-resilient image and video transmission over the Internet using unequal error protection - Kim, Joohee (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2003)
This paper presents a new bit-plane-wise unequal error protection algorithm for progressive bitstreams transmitted over lossy networks. The proposed algorithm protects a compressed embedded bitstream generated by a 3-D SPIHT algorithm by assigning an unequal amount of forward error correction (FEC) to each bit-plane. The proposed algorithm reduces the amount of side information needed to send the size of each code to the decoder by limiting the number of quality levels to the number of bit-planes to be sent while providing a graceful degradation of picture quality as packet losses increase. We also apply our proposed algorithm to transmission of JPEG 2000 coded images over the Internet. To get additional error-resilience at high packet loss rates, we extend our algorithm to multiple-substream unequal error protection. Simulation results show that the proposed algorithm is simple, fast and robust in hostile network conditions and, therefore, can provide reasonable picture quality for video applications under varying network conditions